2007
DOI: 10.1021/jp073280e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Radiationless Transitions:  Effects of Displacement−Distortion−Rotation of Potential Energy Surfaces on Internal Conversion Decay Rate Constants,

Abstract: General expressions for calculating the internal conversion decay rate constants between two adiabatic electronic states and between two diabatic electronic states are derived. The expressions include the displacements, distortions, and rotations of potential energy surfaces as well as the temperature. For illustration, internal conversion rate constants between various singlet electronic states of ethylene and between the first excited S1 and the ground S0 singlet electronic states of azulene are calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Extensive tests on the S 1 ↝ T 1 transitions in thymine, flavone, phenalenone, and free‐base porphyrin have shown that the calculated ISC rates depend only slightly on the particular width of the damping function as long as the VDOS is sufficiently high 136. Along the same lines, general expressions for IC rate constants in the time domain have been derived and applied to various molecular systems 137–140…”
Section: Intersystem Crossing Ratesmentioning
confidence: 97%
See 1 more Smart Citation
“…Extensive tests on the S 1 ↝ T 1 transitions in thymine, flavone, phenalenone, and free‐base porphyrin have shown that the calculated ISC rates depend only slightly on the particular width of the damping function as long as the VDOS is sufficiently high 136. Along the same lines, general expressions for IC rate constants in the time domain have been derived and applied to various molecular systems 137–140…”
Section: Intersystem Crossing Ratesmentioning
confidence: 97%
“…Temperature effects are expected to be particularly large for pairs of states with small singlet‐triplet energy gap 14. In the investigation of (spin‐allowed) radiationless transitions, typically a Boltzmann distribution has been assumed in the excited state 108,138,141,142…”
Section: Intersystem Crossing Ratesmentioning
confidence: 99%
“…TD-FGR has been used to calculate rate constants in quantum processes such as ISC [25,28] and IC [29][30][31][32] and calculated values are known to be in agreement with experiment. However, it has only been applied for unimolecular reactions so far.…”
Section: Adapting Td-fgr For Bimolecular Energy Transfermentioning
confidence: 79%
“…[24] Islampour and Miralinaghi also obtained similar formalism by employing generation function independently in the same year. [47] In 2008, applying TVCF approach, Niu and Shuai further got a more general analytical formalism via abandoning the promoting-mode approximation, [26] and starting from second-order perturbation, Peng et al derived an analytical formalism combining spin-orbit coupling and nonadiabatic coupling for nonradiative decay rate constant between triplet and singlet states. [25] Marian et al investigated the effect of spin-vibronic coupling on the intersystem crossing rate.…”
Section: Hindrance Of Nonradiative Channels In Aggregates the Quantitative Calculation Of Quantum Luminescence Yieldmentioning
confidence: 99%